Graduated compression sleeves: Effects on metabolic removal and neuromuscular performance - Martorelli, S. S.; Martorelli, A. S.; Pereira, M. C.; Rocha-Junior, V. A.; Tan, J. G.; Alvarenga, J. G.; Brown, L. E.; Bottaro, M. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to examine the effects of upper-body graduated compression sleeves (CS) on neuromuscular and metabolic responses during a power training. Fifteen resistance trained men (age: 23.07 ± 3.92 years; body mass: 76.13 ± 7.62 kg; height: 177 ± 6 cm) performed 2 separate power training protocols, either wearing CS or placebo sleeves (PS), in a counterbalanced fashion. Participants first performed a familiarization session and a bench press 1 repetition maximum (1RM) test. The training protocol consisted of 6 sets of 6 repetitions of bench press with a load of 50% 1RM. Statistical analysis compared mean power, peak power, blood lactate, muscle activation, isometric strength, and repetitions to failure. Mean and peak power significantly (p = 0.05) decreased with increasing sets. However, there was no significant difference (p > 0.05) on mean and peak power between protocols. Blood lactate clearance was also not significantly different (p > 0.05) between CS and PS. Muscle activation was not different between PRE and POST (p > 0.05) for any of the muscles analyzed. Isometric strength decreased from PRE to POST (p = 0.05) and was not different between CS and PS. Repetitions to failure were not different between protocols (p > 0.05). These results demonstrate no positive performance effects when wearing graduated CS during power exercise in young trained men.